2007
DOI: 10.1094/fg-2007-1119-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Persistence of Forage and Root-type Chicory Cultivars

Abstract: A challenge in managing chicory (Cichorium intybus L.) as a forage is dealing with bolting of flower stalks in spring. Cultivars of chicory with reduced bolting potential, used mainly for root and sugar production (root types), are available. An experiment was conducted at Rock Springs, PA, to compare forage cultivars and European root‐type cultivars of chicory for yield, bolting, and persistence under clipping. ‘Grasslands Puna,’ ‘Lacerta,’ and ‘Forage Feast’ forage cultivars and ‘Dagerrad,’ ‘Halle,’ and ‘Kat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…In addition to its poor persistence, the amount of stem tissue in Lacerta forage DMY indicated that its nutritive value was probably less than the more leafy cultivars, and this is consistent with reports on nutritive value of whole plants (Labreveux et al, 2006). Poor overall performance of Lacerta is consistent with other studies (Sanderson et al, 2003; Sanderson, 2007) and with the observation that Lacerta functions more like a biennial than a perennial (Foster et al, 2002b; Sanderson, 2007). The apparent intolerance of Lacerta to frequent defoliation when bolting is in conflict with the need to maintain a high leaf proportion for acceptable forage quality, making it an unsuitable cultivar for perennial pasture in Appalachia.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition to its poor persistence, the amount of stem tissue in Lacerta forage DMY indicated that its nutritive value was probably less than the more leafy cultivars, and this is consistent with reports on nutritive value of whole plants (Labreveux et al, 2006). Poor overall performance of Lacerta is consistent with other studies (Sanderson et al, 2003; Sanderson, 2007) and with the observation that Lacerta functions more like a biennial than a perennial (Foster et al, 2002b; Sanderson, 2007). The apparent intolerance of Lacerta to frequent defoliation when bolting is in conflict with the need to maintain a high leaf proportion for acceptable forage quality, making it an unsuitable cultivar for perennial pasture in Appalachia.…”
Section: Discussionsupporting
confidence: 91%
“…Others have also reported differences in frost heaving damage among chicory cultivars, but results are inconsistent. In previous trials at the same research farm in PA where this trial was conducted, Forage Feast and Lacerta heaved more than Puna in one trial (Sanderson, 2007), but not in another (Sanderson et al, 2003). Reasons for this inconsistency among trials and sites are not evident.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations